IMPLEMENTASI PROBLEM BASED LEARNING BERBANTUAN APLIKASI WEB PADA MATERI STATISTIKA - Zuhrotunnisa Zuhrotunnisa; Fitrianto Eko Subekti (IKIP Siliwangi, 2022)
There are many problems faced by students when studying statistics material. These problems cannot be separated from the learning carried out. This article will provide an overview of how to implement Problem Based Learning assisted by web applications. The type of research used is a case study with a quantitative descriptive approach. Collecting data using tests and student response questionnaires. While the data analysis technique used was descriptive statistical test. The results of the learning implementation showed that the students were enthusiastic in participating in the learning carried out and the scores obtained by the students were quite good. However, the next learning process needs to optimize the learning media used and provide more opportunities for students to organize problem-solving, especially for problems that require high-level thinking.